Prenatal Screening for HIV in Nova Scotia: Survey of Postpartum Women and Audit of Current Prenatal Screening Practices - Mark Downing; Laura Youden; Beth A Halperin; Heather Scott; Bruce Smith; Scott A Halperin (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Current guidelines for screening for HIV infections in Nova Scotia recommend an opt-in approach in which patients are counselled and consent to testing. The objectives of the present study were to measure adherence to these recommendations, to explore women's knowledge, attitudes, beliefs and behaviours concerning HIV screening, and to compare these results with prenatal screening practices for rubella, hepatitis B and group B streptococcus.